Revision and phylogenetic analysis of the African genus Ischnopoderona (Scheerpeltz, 1974) new status (Coleoptera, Staphylinidae: Aleocharinae) - Pasnik, Grzegorz (Zootaxa, 2007)
The subgenus Ischnopoderona Scheerpeltz, 1974 is redefined and raised to the genus rank. The revised Ischnopoderona includes 28 species, 12 of which are described as new: Ischnopoderona belingensis sp. n., I. brendelli sp. n., I. densepunctata sp. n., I. frischi sp. n., I. hirtipenis sp. n., I. intermedia sp. n., I. lucidula sp. n., I. micans sp. n., I. reticulata sp. n., I. similis sp. n., I. sinuata sp. n., I. transvaalica sp. n. One new synonym is established: Ischnopoderona madecassa (Cameron, 1944a) = Ischnopoda egregia Pace, 1999a syn. n. Sixteen species are given in new combination: Ischnopoderona aspericollis (Scheerpeltz, 1974), I. capicola (Cameron, 1944), I. externa (Fauvel, 1907), I. gracilicornis (Scheerpeltz, 1974), I. longicollis (Bernhauer, 1931), I. madecassa (Cameron, 1944a), I. nigerrima (Cameron, 1932)(all ex Tachyusa); I. albicornis (Tottenham, 1957), I. brunneipennis (Tottenham, 1957), I. eastopi (Tottenham, 1957), I. interna (Pace, 1995), I. kaszabi (Pace, 1986), I. miricornis (Pace, 1999), I. namibensis (Pace, 1999), I. uhligi (Pace, 1999)(all ex Amanota); I. perinetensis (Pace, 2006) (ex Ischnopoda). Lectotypes are designated for Tachyusa externa Fauvel, 1907, T. longicollis Bernhauer, 1931, T. capicola Cameron, 1944, T. nigerrima Cameron, 1932 and T. madecassa Cameron, 1944. The taxa are diagnosed, keyed and illustrated. The phylogeny of the aleocharine genus Ischnopoderona is analysed using cladistic methods. The monophyly of Ischnopoderona is confirmed and two major monophyletic species groups are recognized.